Sant’Ana dos Olhos D’Água: fé e celebração entre a igreja e o largo (1930-1987) - Oliveira, Rennan Pinto de (2014)
This thesis had as research object the various cultural manifestations in the Festa de Sant’Ana in the twentieth century, between the years 1920-1987. Noteworthy among these cultural manifestations the Festa de Largo, which occurred in the area outside the religious temple, composing some of the steps of the celebration of Senhora Sant’Ana, who is the patroness of the city of Feira Santana. These manifestations of popular and profane character, as the Bando Anunciador, the Lavagem da Igreja, and the Levagem, which were aggregators spaces of a myriad of religious and political expressions, producing diverse cultural practices. Another objective of the analysis was to understand the representations, appropriations and cultural practices undertaken by the participants in the festivities, as well as understand the shock of representations present in the celebrations, resulting from the opposition of the ways the party was experienced by participants ahead to how the festival were idealized by the Catholic Church.